MONITORING OF THE STATUS OF CULTURAL HERITAGE SITES: MONITORING OF THE STATUS OF CULTURAL HERITAGE SITES - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The topic of cultural heritage and its preservation has always been part of the public and professional debate about the development of the regions and their future. In the territorial planning of modern settlements as the duty of specialists is the entry of history into the modern urban structure and spaces. The problems in the management of territories occupied by cultural monuments are dictated rather by the lack of a single and sustainable practice valid for all sites, which ensures security and sustainable development with a balanced protection of the interests of all those affected.